Kontribusi Daya Ledak Otot Lengan Dan Kekuatan Otot Perut Terhadap Ketepatan Smash Atlet Bola Voli Putri SMA NEGERI 04 Bengkulu Utara - Riyono, Riyono; Perdima, Feby Elra; Ferdiansyah, Rahmad (Educative Sportive, 2024)
This study aims to determine the relationship between arm strength and abdominal muscle strength on smash accuracy skills. This research is Quantitative research using Correlation Analysis techniques, The population in this study were 21 athletes from SMA Negeri 04 North Bengkulu. To get the sample in this study was done with total sampling technique. The test of the meaning of the correlation coefficient is carried out by means of the price of rcount with rtable at α = 5% with N = 21. There is a significant relationship between arm muscle strength (X) and abdominal muscle strength (X2) to the skill of smash accuracy. in volleyball athletes at SMA Negeri 04 North Bengkulu, with a value of rxy =0.50> r (0.05) (21) =0.423 and rx2y =0.74>0.423.